THE INFLUENCE OF PRICE AND PRODUCT QUALITY ON PURCHASE DECISION THROUGH E-COMMERCE SHOPEE (CASE STUDY ON STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS - Wisnu Tri Sardi (Scientia Integritas Utama, 2023)
Wisnu Tri Sardi, Rosmaniar, Muh. Ashbar, 2023.Effects of cost and product quality on internet buying decisions (a case study for economics students, Angkaa) A case study involving economics students was used to investigate how product quality and cost influence customer purchasing decisions when shopping online. The research method chosen was a quantitative one. 2020 Economics Faculty students made up the study's population. The sample was created using the Slovin formula, with 87 respondents serving as the number of samples collected using proportionate random sampling. A questionnaire with 8 statements for the pricing variable, 12 for the product quality variable, and 8 for the purchase decision variable was used as the data collection method. and it was determined that every claim was true and reliable. Both primary and secondary data were used. Tools for data analysis include quantitative descriptive analysis, validity testing, reliability testing, multiple regression analysis testing, classical assumption testing (normality, multicollinearity, and heteroscedasticity tests), and hypothesis testing (partial, simultaneous, and coefficient determination tests). employing spss 22. The results of the hypothesis test (t-test) in this study demonstrate that the cost influences business students' online shopping purchasing choices in part. However, simultaneous testing (F-test) demonstrates that price and product quality simultaneously affect purchase decisions made through electronic shopping. Product quality characteristics do not partially influence the online shopping decisions of economics students. Ftable (3.10) > Fcount (26.004) 0.05 and 0.000 respectively, yes.